Duration of larval and pupal development stages of Aedes albopictus in natural and artificial containers - Almério de Castro Gomes; Sabina Lea Davidson Gotlieb; Cristiano C. de Azevedo Marques; Marcia Bicudo de Paula; Gisela Rita A.M. Marques (Universidade de São Paulo, 1995)
Aedes albopictus were reared in different containers: a tree hole, a bamboo stump and an auto tire. The total times from egg hatching to adult emergence were of 19.6,27.3 and 37.5 days, respectively, according to the container. The first, second and third-instar larvae presented growth periods with highly similar durations. The fourth-instar larvae was longer than the others stages. The pupation time was longer than the fourth-instar larvae growth period. The temperature of the breeding sites studied, which was of 18° C to 22° C on average, was also taken into consideration. The mortality of the immature stages was analysed and compared as between the experimental groups; it was lower in the natural containers than in the discarded tire. The average wing length of adult females emerging from tree hole was significantly larger (p < 0.05) than that of those emerging from the tire. Ae. albopictus foi criado em oco de árvore, internódio de bambu e pneu de carro descartável, sob condições de campo. O resultado obtido a partir de larvas recém-nascidas até alado foi de 19,6,27,3 e 37,5 dias. As larvas dos três primeiros estádios tiveram tempo de crescimento similar, não obstante tratar-se de diferentes micro-habitats estudados. Contudo, larvas de 4º estádio apresentaram tempo de duração mais longo e crescente do oco de árvore para o pneu. A temperatura média dos três micro-habitats variou de 18° Ca 22° C. O resultado da taxa de mortalidade encontrada foi menor para larva e pupa do oco de árvore e maior para o pneu. A medida do comprimento médio de asa das fêmeas emergidas do oco de árvore foi maior em relação àquela do pneu.